Nuclear and partonic dynamics in the EMC effect - García Canal, Carlos Alberto (2013)
It has been recently confirmed that the magnitude of the EMC effect measured in the electron deep inelastic scattering is linearly related to the short-range correlation scaling factor obtained from electron inclusive scattering. By using a x-rescaling approach we are able to understand the interplay between the quark-gluon and hadronic degrees of freedom in the discussion of the EMC effect.